STUDI TINGKAT KEANDALAN SISTEM PROTEKSI KEBAKARAN PADA BANGUNAN APARTEMEN (Studi Kasus Apartemen Di Surabaya) - Roy, ADIWIDJAJA, (DIMENSI (Journal of Architecture and Built Environment), 2013)
The reliability condition of fire rescue system is a system built by setting the completeness of site, means of salvation, passive protection system and active protection system for occupants evacuation time and fire fighting in apartment. AHP (Analitycal Hierarchy Process) is used in the process to get the grade in reliability of a buildings security systems. The study is to obtain the value systems of fire and building safety certainty at this stage wheter the use of this building and its environment reliability in accordance with its function and is safe for humans.